PENGARUH HARGA, WORD OF MOUTH DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO 304 MR.D.I.Y SEKETENG SUMBAWA BESAR - Nova Adhitya Ananda; Sulastri (Journal of Management and Business, 2022)
The purpose of this study is, to test whether prices, word of mouth, their image will have any bearing on consumer purchase decision in store MR.D.I.Y Seketeng Sumbawa Besar. This reserch method employs quantitative with an associative approach to primary data types. The population in this study is the sort of homeless who sho in stores MR.D.I.Y Seketeng Sumbawa Besar. The sample in this study is 100 responden and using Paul Leedy. Sampling techniques in this study use non-probability techiques by an overwhelmingly sampling purposive with some of the criteria determined by recearchers. The method of collecting samples on this study USES a quastionnaire and linear regression analysis with SPSS version 26. The results of this study are, (1) prices have a positive and significant impact on purchasing decision in stores MR.D.I.Y Seketeng Sumbawa Besar, (2) word of mouth have a positive and significant impact on purchasing decision in stores MR.D.I.Y Seketeng Sumbawa Besar, (3) brand image have a positive and significant impact on purchasing decision in stores MR.D.I.Y Seketeng Sumbawa Besar.